Domestic Policies and Foreign Resource Requirements: Comment - Edwards, Sebastian (Quarterly Journal of Economics, 1984)
Journal Article Domestic Policies and Foreign Resource Requirements: Comment Get access Sebastian Edwards Sebastian Edwards University of California, Los Angeles Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 99, Issue 1, February 1984, Pages 201–206, https://doi.org/10.2307/1885728 Published: 01 February 1984